1989
DOI: 10.1002/cbf.290070307
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal membrane fluidity and phosphatidylcholine synthesis in rabbit lung under high oxygen tension

Abstract: Phosphatidylcholine metabolism and membrane fluidity were studied in microsomes isolated from rabbit lung, which had been exposed to high oxygen tension for 30 min. In these microsomes the incorporation of [3H]-palmitate into phosphatidylcholine increased whereas the incorporation of [14C]-glycerol and [14C]-choline from CDP-[methyl-14C]-choline remained unchanged in comparison to the control microsomes. The enhanced [3H]-palmitate incorporation may be explained by an increase of the specific activity of acyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…These data are in accordance with those obtained in cultured cells and tissues (1,5,16,29). The increase of membrane fluidity can also be explained by a change in fatty acid lipid composition that causes an increase in free volume between the lipid chains, due to the presence of double bounds in fatty acids (18:2 and 20:4), leading to a bend in the lipid chain itself.…”
Section: Discussionsupporting
confidence: 89%
“…These data are in accordance with those obtained in cultured cells and tissues (1,5,16,29). The increase of membrane fluidity can also be explained by a change in fatty acid lipid composition that causes an increase in free volume between the lipid chains, due to the presence of double bounds in fatty acids (18:2 and 20:4), leading to a bend in the lipid chain itself.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that the PPC could increase liver cell membrane fluidity, microsomal membrane fluidity of the lung, and cell membrane fluidity of erythrocytes. 9,15,37 The results of this study suggest that PPC could not only improve pancreatic acinar cell membrane fluidity and calcium pump activity but could also moderate pancreatic tissue damage caused by decreased OFRs. Further studies are necessary to define the role of PPC, which has shown a broad spectrum of activity.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to the content of cholesterol and proteins as well as the nature and charge of the polar head groups of the phospholipids, membrane fluidity depends on the length of the fatty acid chains of the phospholipids as well as the number and type of their double bonds. 15,16 In the present study, we would like to investigate whether PPC can alter the course of SAP in rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the first, lung homogenates from rats exposed to 100 % oxygen for 24 h showed reduced uptake of oxygen (in the presence of succinate and ADP) compared with homogenates from control animals [9]. In the second, when rabbits underwent ventilation with an increased Fi O2 for 30 min, the lung microsomal phospholipid fatty acid composition was found to be significantly altered [10]. In the third, acid precipitable hydroxyproline was reported to be significantly increased in endobronchial washings from rats after 24 h exposure to 100% oxygen [11].…”
mentioning
confidence: 95%